Del tigre de la ira al tigre del ensueño: William Blake y Jorge Luis Borges - Cabañas Alamán, Rafael (2004)
Even though critics tend to attribute negative and inherent characteristics to William Blake's tiger, in Jorge Luis Borges case this image goes in the opposite direction. Although Borges bears in mind the "tiger of wrath" of his much admired predecessor, the writer adapts the tiger's image with great originality in his poems and brief narrative stories.